Enzyme-Loaded Gel Core Nanostructured Lipid Carriers to Improve Treatment of Lysosomal Storage Diseases: Formulation and In Vitro Cellular Studies of Elosulfase Alfa-Loaded Systems - J. Víctor Álvarez; Carolina Herrero Filgueira; Alexandre de la Fuente González; Cristóbal Colón Mejeras; Andrés Beiras Iglesias; Shunji Tomatsu; José Blanco Méndez; Asteria Luzardo Álvarez; María Luz Couce; Francisco J. Otero Espinar (MDPI AG, 2019)
Mucopolysaccharidosis IVA (Morquio A) is a rare inherited metabolic disease caused by deficiency of the lysosomal enzyme N-acetylgalatosamine-6-sulfate-sulfatase (GALNS). Until now, treatments employed included hematopoietic stem cell transplantation and enzyme replacement therapy (ERT); the latter being the most commonly used to treat mucopolysaccharidoses, but with serious disadvantages due to rapid degradation and clearance. The purpose of this study was to develop and evaluate the potential of nanostructured lipid carriers (NLCs) by encapsulating elosulfase alfa and preserving its enzyme activity, leading to enhancement of its biological effect in chondrocyte cells. A pegylated elosulfase alfa-loaded NLC was characterized in terms of size, ζ potential, structural lipid composition (DSC and XRD), morphology (TEM microscopy), and stability in human plasma. The final formulation was freeze-dried by selecting the appropriate cryoprotective agent. Viability assays confirmed that NLCs were non-cytotoxic to human fibroblasts. Imaging techniques (confocal and TEM) were used to assess the cellular uptake of NLCs loaded with elosulfase alfa. This study provides evidence that the encapsulated drug exhibits enzyme activity inside the cells. Overall, this study provides a new approach regarding NLCs as a promising delivery system for the encapsulation of elosulfase alfa or other enzymes and the preservation of its activity and stability to be used in enzymatic replacement therapy (ERT).